The Effectiveness Of Learning Through Online Applications - Rendi Brahma Fahrezi; Sukma Hendrian; Siti Ainul Kholipah (Jurnal Indonesia Sosial Teknologi, 2023)
Advances in information technology provide a fairly rapid influence in the world of education to improve learning outcomes where the use of IT makes it easier for users to use it anywhere and anytime. One of the desires of students or parents for children's learning outcomes is to obtain optimal grades and be able to support them to achieve their goals. One way is by adding learning through online learning applications that are available in various types. Therefore, researchers want to find out more about the effectiveness of learning through online learning applications. The aim is to find out whether or not the use of online learning applications is effective in improving student learning outcomes at school X Jakarta. The research method used is descriptive quantitative with data collection techniques through the distribution of questionnaires, observations, interviews, and documentation. Respondents were selected by purposive sampling and totaled 40 respondents. The data received will be processed carefully so that the research results show that online learning applications have an effectiveness valued in improving student learning outcomes and the effectiveness of learning through online learning applications is quite good.